Saving lives at birth: The impact of home births on infant outcomes - N. Meltem Daysal; Mircea Trandafir; Reyn van Ewijk (Institute for the Study of Labor (IZA), 2012)
Many developed countries have recently experienced sharp increases in home birth rates. This paper investigates the impact of home births on the health of low-risk newborns using data from the Netherlands, the only developed country where home births are widespread. To account for endogeneity in location of birth, we exploit the exogenous variation in distance from a mother's residence to the closest hospital. We find that giving birth in a hospital leads to substantial reductions in newborn mortality. We provide suggestive evidence that proximity to medical technologies may be an important channel contributing to these health gains.
Keywords: I11; I12; I18; J13; 330; medical technology; birth; home birth; mortality; Geburtenrate; Wohnung; Krankenhaus; Kindersterblichkeit; Kinder; Gesundheit; Niederlande